TRADE AND MARKETING TERMS IN ANCIENT TURKISH - Sevara Xudoyberdiyeva (Web of Journals Publishing, 2023)
Studying the problems of terminology in linguistics to varying degrees dates back to the ancient times of human history. The improvement of trade relations has contributed to the formation and development of economic terms, including marketing terms. In that sense, studying economic terminology also relies on long historical foundations. Today, marketing terminology is being thoroughly studied by world linguists as a relatively new concept. However, it should be noted that the terms of this area, which mean nuclear, are also found in ancient Manuscripts of the Turkish language, are not only called marketing in the industry, and that these terms have been studied in the context of trade terms. Using any new industry and its special terms that enter the country, we have cited the fact that terms that refer to the content and essence of these terms also exist in the history of our language.
Keywords: check, commodity, scientist, berm, debt, sart, sell, aγïr, učuz satig'chi, fig.